Peran Polisi Hutan dalam Menanggulangi Pembalakan Liar/Illegal Logging dalam Kawasan Hutan di Kabupaten Jembrana Provinsi Bali - I Made Adi Endra Supardi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Forests must be managed properly so that their functions and benefits are maintained. One of the problems related to the forestry sector is the large number of illegal logging practices in a number of provinces in Indonesia. Eradication of Illegal Logging in Law of the Republic of Indonesia Number 18 of 2013 concerning the prevention and eradication of forest destruction. This study aims to determine the duties and roles of forest rangers in preventing illegal logging in the forest area of ​​Jembrana Regency and to analyze the obstacle factors of forest rangers in preventing illegal logging in the forest area of ​​Jembrana Regency, Bali Province. This study uses an empirical method with a statutory approach. The data used are primary and secondary data obtained through interviews and documentation. The data obtained were then analyzed through qualitative descriptive. The results showed that the Forestry Police had a role to supervise the implementation of every activity that caused damage to the forest area of ​​Jembrana Regency. Factors that become obstacles in carrying out the role of forest rangers in preventing illegal logging in the Jembrana Regency Forest Area are terrain, facilities and equipment, sincerity, concern and firm commitment, the number of personnel, new methods of crime, and factors of local residents. Forest rangers must involve residents around the forest in an effort to prevent illegal logging considering that the obligation to conserve forests is not only the responsibility of the government but also the responsibility of all forest border residents, especially in Jembrana Regency.